Recovery of Nickel Oxide from Primary-type Portable Spent Battery: an Experimental Strategy - Jha, Vinay K; Miyake, Michihiro (Nepal Journal of Science and Technology, 2012)
In the present work three methods were chosen for the recovery of NiO from primary-type spent battery. In first method, Ni(OH)2 rich fraction of the precipitate was obtained at 7.4 pH after removing the precipitate obtained at pH 4. Second method followed the path of acid (HCl) leached solution treated with sodium hydroxide and thus obtained metal hydroxides which were treated with ammonia solution. Ni(OH)2 solid obtained after evaporation of [Ni(NH3)](OH)2 complex solution was calcinated at 1000°C to get NiO. The method followed the path of acid (HCl) leached solution treated with ammonia solution. Thus obtained [Ni(NH3)](OH)2 complex solution was evaporated till the blue color vanished and then treated with NaOH up to pH 12. The Ni(OH)2 solid after filtration and some more Ni(OH)2 after further heating of liquid solution were dried in oven and then calcinated at 1000°C. Variations of initial amount of battery waste and NH3 concentration were made in order to confirm the degree of efficiency. Third method was found superior in terms of recovery efficiency while second method was better in term of finer and smaller NiO particles. DOI: http://dx.doi.org/10.3126/njst.v12i0.6499 Nepal Journal of Science and Technology 12 (2011) 193-200